CD8+ T Cells Regulate Monopoiesis and Circulating Ly6Chigh Monocyte Levels in Atherosclerosis in Mice. Issue 3 (17th July 2015) - Cochain, Clément; Koch, Miriam; Chaudhari, Sweena M.; Busch, Martin; Pelisek, Jaroslav; Boon, Louis; Zernecke, Alma
<x xml:space="preserve">Abstract</x> Rationale: Proinflammatory adaptive immune responses are recognized as major drivers of atherosclerotic lesion formation. Although CD8+ T cells have recently been proposed as a proatherogenic cell subset, their full scope of actions remains to be elucidated. Objective: We here addressed the contribution of CD8+ T cells to monocyte trafficking in atherosclerosis. Method and Results: We observed that CD8+ T cells express proinflammatory cytokines (interferon-γ, tumor necrosis factor-α, and interleukin-12) within atherosclerotic lesions and spleens of high-fat diet–fed low-density lipoprotein receptor–deficient (Ldlr−/−) mice. Antibody-mediated CD8+ T-cell depletion in high-fat diet–fed Ldlr−/− mice decreased atherosclerotic plaque formation, associated with decreased macrophage accumulation within lesions. Despite a reduction in vascular chemokine (CC-motif) ligand 2 and chemokine (CXC-motif) ligand 1 expression, CD8+ T-cell depletion did not directly affect monocyte recruitment to inflamed vessels. However, CD8+ T-cell depletion decreased chemokine (CC-motif) ligand serum concentrations and circulating Ly6Chigh monocyte counts. We further evidenced that CD8+ T-cell depletion decreased levels of mature monocytes and myeloid granulocyte–monocyte progenitors in the bone marrow and spleen of hypercholesterolemic mice, effects that were partially reproduced by interferon-γ neutralization, showing a role for interferon-γ. Conclusions: These data suggest that CD8+ T cells promote atherosclerosis by controlling monopoiesis and circulating monocyte levels, which ultimately contributes to plaque macrophage burden without affecting direct monocyte recruitment, identifying this cell subset as a critical regulator of proatherogenic innate immune cell responses in atherosclerosis.